Investigation of Precision Grinding Process for Production of Silicon Diaphragms - PEROVA, TANIA (Society of Photo-Optical Instrumentation Engineers, 2002)
The application of precision grinding for the formation of a silicon diaphragm is investigated. The test structures involved 2?6 mm diam diaphragms with thicknesses in the range of 25?150 mm. When grinding is performed without supporting the diaphragm, bending occurs due to nonuniform removal of the silicon material over the diaphragm region. The magnitude of bending depends on the final thickness of the diaphragm. The results demonstrate that the use of a porous silicon support can significantly reduce the amount of bending, by a factor of up to 300 in the case of 50 mm thick diaphragms. The use of silicon on insulator (SOI) technology can also suppress or eliminate bending although this may be a less economical process. Stress measurements in the diaphragms were performed using x-ray and Raman spectroscopies. The results show stress of the order of 13107? 13108 Pa in unsupported and supported by porous silicon diaphragms while SOI technology provides stress-free diaphragms.
PUBLISHED
Keywords: silicon grinding; silicon on insulator; porous silicon; finite element method analysis